(untitled) (Al-Aasar, 2025)
Human psychology, as explored in contemporary science, delves into cognitive processes, emotional regulation, behavioral patterns, and mental well-being through empirical methods and theoretical models. However, contemporary psychology often separates the mind from the soul, overlooking the spiritual and metaphysical dimensions of human behavior. In contrast, Islamic teachings provide a comprehensive, spiritually grounded perspective on human psychology, integrating the physical, mental, emotional, and spiritual aspects of the human being. This paper presents a comparative ethical framework between modern psychological theories and Islamic principles to examine their convergence and divergence on major ethical issues such as human motivation, moral development, self-regulation, and mental health. It argues that while contemporary science offers valuable tools for diagnosis and treatment, Islamic teachings provide a deeper ethical compass and purpose-driven understanding of human behavior rooted in divine accountability, moral responsibility, and inner purification (tazkiyah al-nafs). Key concepts from Islamic scholarship—such as the nafs (self), qalb (heart), ruh (spirit), and ’aql (intellect)—are analyzed in light of psychological constructs like the ego, subconscious, and cognitive behavior. The ethical framework proposed aims to integrate evidence-based psychological practices with values derived from the Qur’an and Sunnah, enabling culturally and religiously informed interventions, especially in Muslim societies. Through this integration, the study suggests a more holistic model for mental health and ethical conduct that aligns with both scientific rigor and spiritual authenticity. The research further advocates for a multi-disciplinary approach, encouraging dialogue between religious scholars and mental health professionals to foster a more inclusive understanding of the human psyche. Ultimately, this comparative analysis contributes to the development of culturally sensitive, ethically grounded, and spiritually meaningful psychological practices.